2013
DOI: 10.1063/1.4773019
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy curves and spin-orbit coupling of light alkali-heavy rare gas molecules

Abstract: The potential energy curves of the X, A, and B states of alkali-rare gas diatomic molecules, MKr and MXe, are investigated for M = Li, Na, K. The molecular spin-orbit coefficients a(R) = are calculated as a function the interatomic distance R. We show that a(R) increases and b(R) decreases as R decreases. This effect becomes less and less important as the mass of the alkali increases. A comparison of the rovibrational properties deduced from our calculations with experimental measurements recorded for NaKr and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
6
0
3
Order By: Relevance
“…This anticipation fits with the calculations of Gervais et al where the SO coupling is examined as a function of the Na-rare gas distance. 8,9 For this reason, the simulation with no SO is included in Fig. 4 for the TV site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This anticipation fits with the calculations of Gervais et al where the SO coupling is examined as a function of the Na-rare gas distance. 8,9 For this reason, the simulation with no SO is included in Fig. 4 for the TV site.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical investigations by Gervais' group in Caen has shown that in alkali (A)-rare gas (RG) pairs, the spin-orbit coupling depends strongly on the alkali-rare gas distance R A−RG . 8,9 The effect is especially large when a light alkali atom (e.g., Na) interacts with a heavy rare gas (e.g., Xe). For instance, considering the energy levels, which correlate with the first 2 P state of the alkali atom at infinite R A−RG separation, the molecular spin-orbit coefficients a(R NaÀXe ) ¼ h 2 Π 1=2 jH SO j 2 Π 1=2 i and b(R NaÀXe ) ¼ h 2 Π À1=2 jH SO j 2 Σ 1=2 i of the Na-Xe pair, vary from +5.7 cm −1 at infinite Na-Xe separation to +27.5 and −21.1 cm −1 , respectively, when R Na−Xe = 3.4 Å.…”
Section: Introductionmentioning
confidence: 99%
“…u -величина относительной скорости резонансной и буферной частиц до столкновения; σ i (u) -транспортное сечение рассеяния поглощающей частицы в состоянии i на буферной частице. Сечения σ i (u) рассчитывались нами по точным формулам классической механики (см., например, [10,11]) с использованием неэмпирических (рассчитанных ab initio) потенциалов взаимодействия для систем сталкивающихся частиц Li−Xe и Na−Xe [12]. Таблично заданные потенциалы взаимодействия интерполировались кубическими сплайнами.…”
Section: численный анализ полевого сужения линии поглощенияunclassified
“…где u T = (2k B T /µ) 1/2 -наиболее вероятная скорость относительного движения поглощающей и буферной Зависимость транспортной частоты столкновений νn(v) от модуля скорости v резонансных атомов при температуре T = 300 K и давлении буферного газа ксенона pXe = 1 Torr для систем сталкивающихся частиц7 Li -Xe (1) и 23 Na -Xe(2). Расчет по потенциалам[12]. Температурная зависимость средних транспортных частот столкновений атомов 7 Li (1) и 23 Na (2) в основном состоянии при их столкновении с атомами Xe при давлении газа ксенона pXe = 1 Torr.…”
unclassified
See 1 more Smart Citation